Development of behavioural automaticity by extended Pavlovian training in an insect. Issue 1894 (16th January 2019) - Mizunami, Makoto; Hirohata, Sho; Sato, Ai; Arai, Ryoichi; Terao, Kanta; Sato, Misato; Matsumoto, Yukihisa
Abstract : The effect of repetitive training on learned actions has been a major subject in behavioural neuroscience. Many studies of instrumental conditioning in mammals, including humans, suggested that learned actions early in training are goal-driven and controlled by outcome expectancy, but they become more automatic and insensitive to reduction in the value of the outcome after extended training. It was unknown, however, whether the development of value-insensitive behaviour also occurs by extended training of Pavlovian conditioning in any animals. Here we show that crickets Gryllus bimaculatus that had received minimal training to associate an odour with water (unconditioned stimulus, US) did not exhibit conditioned response (CR) to the odour when they were given water until satiation before the test, but those that had received extended training exhibited CR even when they were satiated with water. Further pharmacological experiments suggested that octopamine neurons, the invertebrate counterparts of noradrenaline neurons, mediate US value signals and control execution of CR after minimal training, but the control diminishes with the progress of training and hence the CR becomes insensitive to US devaluation. The results suggest that repetitive sensory experiences can lead to a change from a goal-driven response to a more automatic one in crickets.